Using Musical Activities in Primary School Subjects - Stramkale, Ligita (Journal of Education Culture and Society, 2025)
Aim. The study aims to determine the opinions of primary school teachers about the use of musical activities in the subjects taught in grades 1-3 of primary education.Methods. The study used a quantitative research design and involved 151 (N=151) primary school teachers who completed a questionnaire at five different time points. The study addressed three research questions: RQ1: What types of musical activity could primary school teachers use in other subjects? RQ2: In which subjects could primary school teachers use musical activities? RQ3: At what level can primary school teachers use musical activities in each of the subjects taught in grades 1-3 of primary school? SPSS version 22 was used for statistical data analysis to group the data, observe trends, and establish relationships between variables.Results. The study revealed that primary school teachers often use musical activities such as listening to music in other subjects but play musical instruments the least. English, sports, and Latvian are the most common subjects where musical activities are used, while design and technology are the least. Although primary school teachers can use musical activities at a high level in several subjects, English is the most highly-rated subject, while the lowest-rated subject is design and technology.Conclusions. The findings allow us to determine which types of musical activities could be used in grades 1-3 of primary education, in which subjects the teachers most often use musical activities, and at what level primary school teachers evaluate their ability to do that.